2003
DOI: 10.1161/01.cir.0000059939.97249.2c
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Function of a Biological Pacemaker in Canine Heart

Abstract: Background-We hypothesized that localized overexpression of the hyperpolarization-activated, cyclic nucleotide-gated (HCN2) pacemaker current isoform in canine left atrium (LA) would constitute a novel biological pacemaker. Methods and Results-Adenoviral constructs of mouse HCN2 and green fluorescent protein (GFP) or GFP alone were injected into LA, terminal studies performed 3 to 4 days later, hearts removed, and myocytes examined for native and expressed pacemaker current (I f ). Spontaneous LA rhythms occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
187
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(194 citation statements)
references
References 17 publications
5
187
0
2
Order By: Relevance
“…To date, there are only 3 in vivo examples of the concept: our original report of AV nodal gene transfer in sedated pigs with acute AF and 2 illustrations of genetic pacemaker activity. 7,16,17 In the current report, we continue the process of developing gene therapy as a potential option for cardiac arrhythmias. In a stepwise fashion, we first showed rate control in an acute model of AF, 7 and now we demonstrate rate control in a physiologically relevant model of persistent AF and severe chronic heart failure.…”
Section: Discussionmentioning
confidence: 98%
“…To date, there are only 3 in vivo examples of the concept: our original report of AV nodal gene transfer in sedated pigs with acute AF and 2 illustrations of genetic pacemaker activity. 7,16,17 In the current report, we continue the process of developing gene therapy as a potential option for cardiac arrhythmias. In a stepwise fashion, we first showed rate control in an acute model of AF, 7 and now we demonstrate rate control in a physiologically relevant model of persistent AF and severe chronic heart failure.…”
Section: Discussionmentioning
confidence: 98%
“…If current, also called a "pacemaker current", is the inward current during the diastolic phase, resulting in spontaneous rhythmic activity. 19,20 The adenoviral gene transduction of HCN2 channel induced pacemaker ac- tivity in the atrium 21 and the left bundle branch. 22 These initial trials revealed that a gene transfer into cardiomyocytes evoked spontaneous activity, but the heart rate as a result of these biological pacemakers was relatively low.…”
Section: Gene Therapymentioning
confidence: 99%
“…1 For example, in the context of cardiac impulse generation and propagation, focal gene transfer has recently been reported to result in both the creation of biological pacemakers 2,3 and conduction slowing through the atrioventricular (AV) node. 4 The essential physiological properties of cardiomyocytes supporting efficient myocardial impulse propagation are an excitable cell membrane and capacity for gap junctional intercellular communication (GJIC).…”
mentioning
confidence: 99%